Reversible in vitro growth of Alzheimer disease beta-amyloid plaques by deposition of labeled amyloid peptide. - Maggio, J E (1992)
The salient pathological feature of Alzheimer disease (AD) is the presence of a high density of amyloid plaques in the brain tissue of victims. The plaques are predominantly composed of human beta-amyloid peptide (beta A4), a 40-mer whose neurotoxicity is related to its aggregation. Radioiodinated human beta A4 is rapidly deposited in vitro from a dilute (less than 10 pM) solution onto neuritic and diffuse plaques and cerebrovascular amyloid in AD brain tissue, whereas no deposition is detectable in tissue without performed plaques. This growth of plaques by deposition of radiolabeled beta A4 to plaques is reversible, with a dissociation half-time of approximately 1 h. The fraction of grey matter occupied by plaques that bind radiolabeled beta A4 in vitro is dramatically larger in AD cortex (23 +/- 11%) than in age-matched normal controls (less than 2%). In contrast to the human peptide, rat/mouse beta A4 (differing at three positions from human beta A4) does not affect the deposition of radiolabeled human beta A4. beta A4 has no detectable interaction with tachykinin receptors in rat or human brain. The use of radioiodinated beta A4 provides an in vitro system for the quantitative evaluation of agents or conditions that may inhibit or enhance the growth or dissolution of AD plaques. This reagent also provides an extremely sensitive method for visualizing various types of amyloid deposits and a means for characterizing and locating sites of amyloid peptide binding to cells and tissues.